The Language and Doctrine of Desire in Julian of Norwich's Revelations - Pezzini, Domenico (Cistercian studies quarterly, 2011)
A literary criticism of the book "Revelations of Devine Love," by Julian of Norwich is presented. It explores the writing style of the author including meaning of the words desire and wish which are frequently used in the book. It mentions that Julian expresses God's desire and longing through the line "Jesus' thirst." It adds that the book is scholarly with recurring sentences and full of contemplation.